2022
DOI: 10.1039/d2fo00578f
|View full text |Cite
|
Sign up to set email alerts
|

Development if healthy milk and yogurt products for reducing metabolic diseases using cyclodextrin and omega-3 fatty acids from fish oil

Abstract: The food industry is constantly attempting to develop better products that will have a positive effect on health. Feiraco® and Clesa®, expressed their intention to create novel products using UNICLA®...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Recently, many studies reported that yogurt is considered one of the most important food products that can be compatible with other food ingredients. Besides, the addition of natural functional ingredients to yogurt has significantly gained consumers' acceptance because of the health benefits of both yogurt and natural functional ingredients (Table 1) (Ahmad et al 2023;Basiri et al 2022;Guadarrama-Flores et al 2022;Huang et al 2022;Rashwan et al 2022;Shahein et al 2022;Tami et al 2022;Tang et al 2022).…”
Section: Natural Functional Ingredientsmentioning
confidence: 99%
“…Recently, many studies reported that yogurt is considered one of the most important food products that can be compatible with other food ingredients. Besides, the addition of natural functional ingredients to yogurt has significantly gained consumers' acceptance because of the health benefits of both yogurt and natural functional ingredients (Table 1) (Ahmad et al 2023;Basiri et al 2022;Guadarrama-Flores et al 2022;Huang et al 2022;Rashwan et al 2022;Shahein et al 2022;Tami et al 2022;Tang et al 2022).…”
Section: Natural Functional Ingredientsmentioning
confidence: 99%
“…A recent study found that yoghurt fortified with PUFAs showed neuroprotective effects against aluminium-chloride-mediated neurotoxicity and enhanced brain dopamine and serotonin [24]. Also, yoghurts fortified with EPA and DHA showed high bioaccessibility values as a result of efficient intestinal absorption [25]. Other dairy products fortified with omega-3 fatty acids [26][27][28] and other functional lipids have been reported (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Different technologies have been proposed to functionalise highly consumed foods, such as dairy products, with PUFA. Total and partial milk fat replacement have been investigated to incorporate both vegetable and fish oils in different types of yogurts (Dal Bello et al ., 2015; Zhong et al ., 2018; Ardabilchi Marand et al ., 2020; Ghorbanzade et al ., 2022; Guadarrama‐Flores et al ., 2022; Suwannasang et al ., 2022). Direct incorporation of oils, flours, seeds, nuts and fruit pulps rich in PUFA, as well as the addition of rich PUFA oils in form of emulsions, micro‐ and/or nano‐encapsulates at the different stages of the yogurt manufacturing process have been proposed (Vanegas‐Azuero & Gutiérrez, 2018; Gumus & Gharibzahedi, 2021).…”
Section: Introductionmentioning
confidence: 99%